1994
DOI: 10.1056/nejm199406233302501
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training and Nutritional Supplementation for Physical Frailty in Very Elderly People

Abstract: High-intensity resistance exercise training is a feasible and effective means of counteracting muscle weakness and physical frailty in very elderly people. In contrast, multi-nutrient supplementation without concomitant exercise does not reduce muscle weakness or physical frailty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
1,584
11
84

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,524 publications
(1,775 citation statements)
references
References 27 publications
59
1,584
11
84
Order By: Relevance
“…Perhaps more importantly, in such drug studies a finding that joint pain relief is not associated with improved walking velocity can be explained by the fact that 1 here was not sufficient time for improvement in muscle function to occur, even though the joints were less inflamed and painful. These findings are also consistenl with observations by other investigators that strengthening of lower extremity muscles can improve one's ability to ambulate efficiently (12,13).…”
Section: Discussionsupporting
confidence: 87%
“…Perhaps more importantly, in such drug studies a finding that joint pain relief is not associated with improved walking velocity can be explained by the fact that 1 here was not sufficient time for improvement in muscle function to occur, even though the joints were less inflamed and painful. These findings are also consistenl with observations by other investigators that strengthening of lower extremity muscles can improve one's ability to ambulate efficiently (12,13).…”
Section: Discussionsupporting
confidence: 87%
“…We showed that mitochondria are damaged within cells instead of being frail and damaged during the isolation procedure. A functional muscle that has not lost the capacity to synthesize healthy mitochondria is an important contributor to the prevention of frailty, a major problem in medicine, particularly in geriatrics (Fiatarone et al 1994;Gill et al 2010). Thus, understanding the molecular mechanisms of mitochondriogenesis in aging has both theoretical and practical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle aging is a key component of the increase in frailty in human and animal populations (Vanitallie 2003). Physical exercise is an obvious antiaging mechanism and it is intended to serve as a prevention of cardiovascular aging but also as a prevention of sarcopenia as well as loss in muscle functionality (Fiatarone et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In the positive direction, people who are ®t tend to be physically active, and people with chronic diseases who enter an exercise program demonstrate an increase in their physical activity outside of the training program. Studies from our laboratory have previously shown this for adults with rheumatoid arthritis (Rall et al, 1996a, b), HIV infection (Roubenoff et al, 1997b), as well as for frail elderly nursing home residents (Fiatarone et al, 1994). In the negative direction, as people become weaker, either because of disease or because of age-related sarcopenia, the proportion of maximal effort required to perform daily tasks increases, so that it becomes progressively uncomfortable to perform these tasks, and they are abandoned.…”
Section: Impact Of Sarcopeniamentioning
confidence: 93%